2019
DOI: 10.1021/acsomega.8b03069
|View full text |Cite
|
Sign up to set email alerts
|

Nonoxidative Dehydrogenation of Methanol to Methyl Formate through Highly Stable and Reusable CuMgO-Based Catalysts

Abstract: Nonoxidative dehydrogenation of methanol to methyl formate over a CuMgO-based catalyst was investigated. Although the active site is metallic copper (Cu 0 ), the best reaction conditions were obtained by tuning the ratio of Cu/Mg and doping the catalyst with 1 wt % of Pd to achieve a very specific activity for methyl formate synthesis. On the basis of the CO 2 temperature-programmed desorption study, the basic strength of the catalyst plays a role in the efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…These precious metals were chosen because of their extensive use in industrial catalysis. There is a small peak (44.4°) just next to (200) peak of HEO as shown in Figure a. This peak may be the bimetallic oxides alloys (CuMgOx, CoMgOx, CuCoOx, NiCoOx) as reported. After addition of PtO 2 or RuO 2 into the precursors, mechanochemical grinding was performed and a single phase of rock salt HE oxide was observed. XRD confirmed that no diffraction peaks attributed to Pt or Ru metal or binary metal oxides were present in the 2 h milled samples , as shown in Figure b.…”
mentioning
confidence: 93%
“…These precious metals were chosen because of their extensive use in industrial catalysis. There is a small peak (44.4°) just next to (200) peak of HEO as shown in Figure a. This peak may be the bimetallic oxides alloys (CuMgOx, CoMgOx, CuCoOx, NiCoOx) as reported. After addition of PtO 2 or RuO 2 into the precursors, mechanochemical grinding was performed and a single phase of rock salt HE oxide was observed. XRD confirmed that no diffraction peaks attributed to Pt or Ru metal or binary metal oxides were present in the 2 h milled samples , as shown in Figure b.…”
mentioning
confidence: 93%
“…There was a noticeable increase in methanol conversion from 15% (0.3 mol of H 2 /mol of methanol with the ex -Ru catalyst) to 30% (0.6 mol of H 2 /mol of methanol) in the presence of in -Ru catalyst. Further, we observed that the temperature and base play a pivotal role in tuning the catalytic methanol to H 2 conversion over the in -Ru catalyst (Figures S1 and S2 of the Supporting Information). A decline in catalytic activity was noted when employing a lower content of KOH (0.55 equiv) (entry 3 in Table ). Conversely, enhanced hydrogen production (135 mol of H 2 /mol of Ru and 0.8 mol of H 2 /mol of methanol) was observed with 2.1 equiv of KOH at 110 °C, which is 1.4-fold higher than that observed with 1.2 equiv of KOH (entries 2 and 4 in Table ).…”
mentioning
confidence: 95%
“…It is generally accepted that metallic Cu species are the active sites for methanol dehydrogenation. [39][40][41][42][43] Yang et al performed mechanistic studies of methanol dehydrogenation to MF over Cu-based catalyst and they found that methanol is first dehydrogenated over Cu 0 sites to formaldehyde (FA). [41] MF is then formed by the reaction of FA with surface methoxy species over Cu 0 sites and not via the Tishchenko mechanism (i. e., the dimerization of two FA molecules).…”
Section: Introductionmentioning
confidence: 99%